1998
DOI: 10.1121/1.423273
|View full text |Cite
|
Sign up to set email alerts
|

Ground influence on the definition of single rating index for noise barrier protection

Abstract: A single number rating index to qualify the acoustical protection of a noise barrier that accounts for the influence of the ground is developed. This is an extension of a previous index for semi-infinite barrier developed by Pfretzschner ͓Pfretzschner et al., Acust. Acta Acust. 82, 504-508 ͑1996͔͒. This index is based on the asymptotic value found for the insertion loss or the acoustic attenuation as physical magnitude, and it is uniquely dependent on the barrier, noise source, and acoustic characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…So, in works [1,2] it is shown that the efficiency of noise barriers depends on the type of sound source, frequency and relative position of the barrier source and the design point. Works [3,4] show a significant effect of the earth's surface on the efficiency of barriers. Studies [5] show the influence of the shape of the barrier on its efficiency, and this influence significantly depends on the frequency and on the relative position of the sound source and the calculated point.…”
Section: Introductionmentioning
confidence: 99%
“…So, in works [1,2] it is shown that the efficiency of noise barriers depends on the type of sound source, frequency and relative position of the barrier source and the design point. Works [3,4] show a significant effect of the earth's surface on the efficiency of barriers. Studies [5] show the influence of the shape of the barrier on its efficiency, and this influence significantly depends on the frequency and on the relative position of the sound source and the calculated point.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, experimental studies were carried out only on single barriers [6] without taking into account other reflective surfaces, such as the surface of the earth and roads. Later, studies of the sound field around the barrier were carried out taking into account the influence of the reflective surfaces of the road and the ground [7]. However, these studies were based on the geometric theory of sound propagation, and therefore had a rather narrow field of application.…”
Section: Research Of Existing Solutions To the Problemmentioning
confidence: 99%
“…It is worth noticing that in Equation (8) there are two terms that contribute to the propagation of the diffracted field. The former corresponds to the attenuation due to geometrical divergence, whereas the latter corresponds to the angular field distribution assuming that the top end of the screen acts as a secondary source with a directivity D defined in Equation (8). The insertion loss may then be given by:…”
Section: Relationship With the Diffraction Coefficientmentioning
confidence: 99%
“…7 If more complex situations had been considered, for instance ground reflection or barriers with different top end structures, the same expression would be obtained where IL ¥,i would correspond to the new situation. 8 2. PHYSICAL SIGNIFICANCE OF THE ASYMPTOTE As stated above, the sound reduction index of a barrier may be defined in terms of the asymptote of Equation (1) when the distance r between barrier and receiver tends to infinity.…”
Section: Introductionmentioning
confidence: 99%